Glamorize Beauty / Farzana Mohamad Musa and Nurul Hazaleena Razali - Mohamad Musa, Farzana; Razali, Nurul Hazaleena (2022)
Glamorize Beauty is a partnership business that sells cosmetics run by Farzana Binti Mohammad Musa and Nurul Hazaleena Binti Razali. We both are native of Selangor who have just started running a Sobella brand cosmetics business. In April 2022, we became a Sobella Cosmetics brand agent and successfully managed to get customers who bought the product. Among the products we sell under the Sobella brand include lip matte, lip tint, eyeshadow, blusher, and foundation at a very affordable price for people to buy. Nowadays, social media sites like Facebook are crucial since they may assist new businesses to promote their business. As we all know, a majority of people use it, regardless of age or gender. So, it is easy for a new business owner like us to attract customers, whether they are aware of us or not, and this indirectly helps our company grow. To draw customers' interest, we can publish teasers, soft sells, and hard sells on this Facebook page. Customers can get a lot of information and promotions about our product by simply clicking on our page. We also provide a Whatapps phone number in case they have any questions about the product. In addition, we can keep track of how often we post and how many people are visiting our page thanks to the Facebook page. Furthermore, if we are unable to post on that day, we can schedule posting so that we can continue to update for customers who want to know more about the product or any promotions.